Deconvoluting sources of failure in lithium metal batteries containing NMC and PEO-based electrolytes. (1st February 2022) - Hawley, W. Blake; Du, Zhijia; Kukay, Alexander J.; Dudney, Nancy J.; Westover, Andrew S.; Li, Jianlin
Highlights: Sudden, rapid capacity fade observed in cells with gel polymer electrolyte. Cyclic voltammetry suggests good stability between NMC and gel polymer electrolyte. Li dendrites and instability with gel polymer electrolyte are of primary concern. Capacity fade due to cathode can be partially overcome with better cathode design. Abstract: Solid-state lithium metal batteries (SSLMBs) containing polyethylene oxide (PEO)-derived polymer electrolytes and high-voltage (> 4 V vs. Li/Li + ) cathode materials suffer from three sources of failure: (1) instability between the polymer electrolyte and cathode at high voltage, (2) instability of the polymer electrolyte with Li metal, and (3) poorly-designed cathodes. In this study, these three sources of failure are deconvoluted by studying Ni-rich LiNix Mny Co1-x-y O2 (NMC, x ≥ 0.6) cathodes and a gel polymer electrolyte (GPE) derived from PEO. Initial cycling data reveals that rapid capacity fade occurs regardless of whether soft short circuits form due to Li dendrites. Cyclic voltammetry scans on cells featuring a Li metal electrode, GPE, and a NMC811 electrode free of additives suggest that there are no runaway reactions between the GPE and NMC811 up to 4.5 V vs. Li/Li + . Cathode/cathode symmetric cell cycling demonstrates that Li metal reactivity is a prime source of failure, though a poorly-designed cathode leads to subpar performance. A cathode with single-crystal NMC particles was demonstrated to achieve better initial capacity and longer cycle life, indicating room for improvement in SSLMB cathode design. Therefore, the sources of failure as enumerated may be ranked as follows from most to least concerning: 2 > 3 > 1.